FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEPUTIHAN PADA WANITA USIA SUBUR (WUS) DI KECAMATAN BANJAREJO KOTA MADIUN - Ika Ayu Purnamasari; Amelia Nur Hidayanti (The Shine Cahaya Dunia S-1 Keperawatan, 2019)
Background; Leucorrhea can be a normal state (physiological) or abnormal conditions (pathological). In the pathological leucorrhea, if it not promptly treated, it can lead to infertility and pregnancy outside the womb even whitish is the early symptom of cervical cancer that can lead to dead. The purpose of this study to know the factors associated with occurrence of leucorrhea on fertile women.Method; It use descriptive research with cross sectional correlation. The sampling technique used simple random sampling technique with a standard error of 5%. The sample Population samples was 56 respondens, the factors related to the occurrence of the leucorrhea accurence and whiteness were measured by questionnaires. Statistical test used chi square test.Result; There is a relationship between the use of contraception with the occurrence of leucorrhea (p-value = 0,037 ), there is no correlation between the use of pantyliner with leucorrhea accurance (p-value = 0,581 ), there is a correlation between the use of vaginal douche with the incidence of leucorrhea (p-value = 0,000 ), there is a relationship between personal hygiene with the incidence of leucorrhea (p-value = 0,002) on fertile age women Desa Sidoharjo, Kecamatan Banjarejo kota Madiun.Conclusion; Thus it is expected to health personnels to provide information about reproductive health, especially the factors that cause leucorrhea.Â Keyword: leucorrhea, fertile women